Implementation of the E-Government System: A case study at the Ministry of Religious Affairs Office in Sukabumi City - Jalaludin, Ludi (International Journal of Educational Research Excellence (IJERE), 2023)
The purpose of this study is to determine the advantages and disadvantages of the e-government system, obstacles in the implementation of the e-government system, and the implementation of the e-government system at the Office of the Ministry of Religious Affairs in Sukabumi City. The data collection technique is carried out through observation, interviews, and documentation. The location of the study was focused on the Ministry of Religious Affairs of Sukabumi City. The respondents in this study were 9 employees of the Ministry of Religious Affairs of Sukabumi City. Data analysis is carried out by selecting answers obtained from respondents and then collected for analysis and conclusions. The data analysis used is data triangulation. The results of the study were obtained, 1) The advantages of the e-government system are to facilitate public services and public services more effectively and efficiently, while the disadvantages of the e-government system are service procedures and one-stop integrated service media (PTSP). 2) Obstacles in the implementation of PTSP at the Ministry of Religious Affairs office in Sukabumi City include inadequate facilities and infrastructure, and lack of human resources in implementing PTSP and SOPs. (3) The implementation of the e-government system at the Ministry of Religious Affairs office has been going well even though in practice there are obstacles faced, namely the many types of applications used in integrating one-stop integrated services (PTSP).